Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/age.12029
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of coat colour variations in White Galloway and White Park cattle

Abstract: White Galloway cattle exhibit three different white coat colour phenotypes, that is, well marked, strongly marked and mismarked. However, mating of individuals with the preferred well or strongly marked phenotype also results in offspring with the undesired mismarked and/or even fully black coat colour. To elucidate the genetic background of the coat colour variations in White Galloway cattle, we analysed four coat colour relevant genes: mast/stem cell growth factor receptor (KIT), KIT ligand (KITLG), melanoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 18 publications
4
54
0
6
Order By: Relevance
“…Region B8 contains the MC1R gene near the peak at 14.0-15.0 Mb position on BTA-18, where strong selection signatures have previously been identified involving several breeds that have also been used in the present study [15]. The melanocortin 1 receptor ( MC1R ) gene is the candidate for coat colour in cattle [13,15,20,72,73]. …”
Section: Discussionmentioning
confidence: 99%
“…Region B8 contains the MC1R gene near the peak at 14.0-15.0 Mb position on BTA-18, where strong selection signatures have previously been identified involving several breeds that have also been used in the present study [15]. The melanocortin 1 receptor ( MC1R ) gene is the candidate for coat colour in cattle [13,15,20,72,73]. …”
Section: Discussionmentioning
confidence: 99%
“…During the investigation we excluded several animals that were reported as belted by the owners, but had only minimal white spots that did not resemble the typical belt phenotype. We also excluded several animals that were reported as non-belted by the owners, but turned out to be White Galloways, on which a belt would not have been visible [35]. The final cohort thus consisted of 333 belted animals and 1,322 non-belted cattle.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a number of studies indicate a chromosomal translocation (and subsequent duplication) of the KIT gene in several cattle coat phenotypes ( Figure 2B ; Durkin et al, 2012; Brenig et al, 2013). Durkin et al (2012) found that a 492 kbp segment of BTA6 containing the KIT gene was translocated to BTA29 in several Brown Swiss and Belgian Blue cattle via two circular intermediate steps, and a reshuffling of the order of genes on the transferred segment.…”
Section: The Evolutionary and Functional Impacts Of Cnvs In Livestockmentioning
confidence: 99%
“…While the translocation and incorporation of DNA circular intermediates has been well characterized in bacterial integron dynamics (Domingues et al, 2012), this is one of the first instances where a similar mechanism was detected in a mammalian species, let alone a complex double-translocation event. The implications of this new allele have extended beyond Brown Swiss and Belgian Blue cattle as White Galloway and White Park cattle were found to carry this allele (Brenig et al, 2013). Surprisingly, the effects of the modified KIT locus in these cattle result in mottled markings rather than color-sidedness, suggesting that the extent by which modification of KIT can influence coat color has not been fully explored (Brenig et al, 2013).…”
Section: The Evolutionary and Functional Impacts Of Cnvs In Livestockmentioning
confidence: 99%
See 1 more Smart Citation